Reconstructing the invasion of Cyperus esculentus in Central Europe. (9th March 2015) - Follak, S; Aldrian, U; Moser, D; Essl, F; Novak, Stephen
Summary Cyperus esculentus (yellow nutsedge) is a serious weed in agriculture worldwide and observational data suggest that it has recently started to spread rapidly in Central Europe. We studied its spatiotemporal invasion pattern, rate of spread and habitat affiliation in Austria, Germany and Switzerland, using retrospective distribution data from various sources and a method that accounts for sampling bias. In total, we found 265 records of C. esculentus since 1900. Multiple accidental introductions, coupled with subsequent regional radial expansion, describe the spatiotemporal range expansion of C. esculentus in the study area. Cumulative number of records and of the number of invaded grid cells showed a continuous increase, but spread has become more pronounced recently (>2005). Invasion hotspots were located in the warmest regions of the study area, as well as in regions with an oceanic climate. On average, the rate of spread within these invasion hotspots ranged between 3.1 and 5.7 km per year. Cyperus esculentus was primarily found on arable land, while other habitats have been rarely invaded. The integration of different data sources improved the cover of distribution data and was useful for reconstructing the incipient and recent invasion phase of C. esculentus. The data suggest that control may be best achieved by preventing long‐range dispersal and containing or eradicating incipient infestations of C. esculentus.